2020
DOI: 10.31219/osf.io/b6hpx
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Bilingual acoustic voice variation is similarly structured across languages

Abstract: When a bilingual switches languages, do they switch their "voice"? Using a new conversational corpus of speech from early Cantonese-English bilinguals (N = 34), this paper examines the talker-specific acoustic signature of bilingual voices. Following prior work in voice quality variation, 24 filter and source-based acoustic measurements are estimated. The analysis summarizes mean differences for these dimensions, in addition to identifying the underlying structure of each talker's voice across languages with p… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 20 publications
1
6
0
Order By: Relevance
“…The method used in this survey is adapted from the works of Johnson et al (2020), , and Lee & Kreiman (2022) on analyzing the voice-quality-related parameters. All analyses were carried out using R version 4.0.4 (R Core Team, 2021)…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The method used in this survey is adapted from the works of Johnson et al (2020), , and Lee & Kreiman (2022) on analyzing the voice-quality-related parameters. All analyses were carried out using R version 4.0.4 (R Core Team, 2021)…”
Section: Discussionmentioning
confidence: 99%
“…The first four formant frequencies (F1, F2, F3, F4): the first four formant frequencies are associated with the transfer function of the vocal tract (Kreiman et al, 2014). The first three formants are commonly employed when discussing the linguistic variations in different languages and the fourth formant is mostly referred to as a speaker-specific parameter (Johnson et al, 2020) H1*-H2*1, H2*-H4*, H4*-H2kHz*, and H2kHz*-H5kHz: all these parameters are associated with the spectral shape of the harmonic source. H1*-H2* denotes the difference between the amplitude of the first and the second harmonics and gauges the harmonic slope which is indicative of the phonation type.…”
Section: Acoustic Parametersmentioning
confidence: 99%
See 2 more Smart Citations
“…However, building mental models of individual voice spaces requires substantial experience with specific talkers. Lacking wide familiarity with how a person's voice varies across changing contexts, it is challenging to recognize that two voice samples come from the same talker ("telling voices together"; Johnson et al, 2020;Lavan et al, 2019b). Consistent with this view, recent evoked potential data (Plant-H ebert et al, 2021) showed that responses to familiar and unfamiliar voices vary with time window as well as familiarity status, implying a two-step process beginning with the evaluation of shared features, and moving on to incorporation of idiosyncratic features as needed for familiar voices.…”
Section: Discussionmentioning
confidence: 99%